Exercising older people ́s brains in Costa Rica: Design principles for using information and communication technologies for cognitive activity and social interaction - Castro Rojas, María Dolores (2018)
This study is part of a design-based research project aimed at designing a learning intervention for enabling Costa Rican older people to use informa- tion and communication technologies for cognitive activity and social interaction. Data from relevant literature, a focus group with older adults, and interviews with professionals teaching older adults how to use informa- tion and communication technologies were analyzed, in order to create context-sensitive design principles that could guide the design of learning interventions that meet the needs of older learners. The analysis derived context-sensitive design principles that include wider topics that influence the learning process, such as emotions and stereotypes related to learning about and using information and communication technologies, as well as the social support to that learning. The resulting eight design principles argue for respectful learning environments, in-depth comprehension of changes related to aging, time and space to reflect on emotions related to the learning process, and acknowledgment of participants’ individuality.